Business models for scaling Climate Smart Agriculture in Bihar, India - Vernet, Pierre Antoine (2017)
Bihar is one of the poorest, most populous states in India. The populations are mainly rural dwellers and are dependent on agriculture production, as a means of subsistence and as revenue. Bihar (or more generally the entire eastern Indo Gangetic Plains of India) is composed of small scale (less than a hectare) and fragmented farm holding with poor access to new technologies. (Arya J.P. 2015) As well as being extremely vulnerable to climate change and frequent climatic aberrations (floods, drought and weather volatility), Bihar is also hindered by natural resource degradation and a lack of knowledge and development opportunities. (S.Lopez Ridaura 2014, NAFCC 2016) Introducing climate-smart practices and technologies to male and female farmers and promoting business models with the best upscaling potential can increase the resilience and adaptive potential of agriculture in Bihar. Farmer’s adoption of CSA technologies and practices could be enhanced through the involvement of CSA service providers or entrepreneurial farmers. Indeed, sustainable business models linking farmers and private sector have the potential to benefit all CSA-value chain stakeholders. CSA practices provide both farmers and service providers with the opportunity to better manage risks, to save labor and costs and to increase revenues. (Sharma 2015) To determine the feasibility of this research, a socio-economic survey will be carried out in the Samastipur and Vaishali District of Bihar on 17 different service providers (i.e. small businesses) leasing or providing CSA technologies and machineries. This MSc Climate change, Agriculture and Food Security (CCAFS) research project will identify existing and potential business models that can support scaling-up and scaling-out of CSA practices and technologies in Bihar. These business models will be assessed using the business model canvas as it presents the global strategy to a well-established business. It details all parts of the company, showing revenues, costs, preconditions and partnerships required but it also underlines potential risks and benefits of the business for all stakeholders. (Groot 2016) Templates of the canvas business model will be incorporated into the analysis. It will allow us to evaluate current and potential effects of the adoption of business models promoting CSA practices and technologies, on both service providers (SPs) and customers (male and female farmers). (Groot 2016) This project “Business models for scaling Climate Smart Agriculture in Bihar, India” is part of the CCAF-CGIAR project P53-FP1-SA-CIMMYT “Recommendation domains incentives and institutions for equitable local adaptation planning at sub-national level and scaling up CSA practices in wheat and maize systems”.